HUBUNGAN ANTARA KARAKTERISTIK IBU DAN PEMBERIAN ASI EKSKLUSIF - ., I Gusti Putu Felik (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: World Health Organization recommended exclusive breastfeeding for six months. Exclusive breastfeeding rate was relativelylow in some regions. Factors influencing exclusive breastfeeding need tobe identified. This study aims to estimate the prevalence and the mother’scharacteristic influencing exclusive breastfeeding.Method: This study was a retrospective cross-sectional study. The studywas performed in a population of mothers who have baby aged 6-24months in Puskesmas Sungai Raya Dalam. A total of 104 samples wereobtained by questionnaire and interview.Result: In this study, the prevalence of infants who ever breastfed was95%, the infants who had an exclusive breastfed 2%, and 79% wasbreastfed more than six months old. Prevalence of giving complementaryfood before infant aged six months old was 98% and giving prelacteal foodwas 50%. Most of the infants were given complementary food at aged 0-7days old (72%). Most of mothers were aged 26-35 years old (48%),unemployed (90%) and had a low educational background (57%),prosperous lives (81%) and primiparous (52%). Mother’s characteristics(mother’s age, work hours, education level, prosperity and parity) were notassociated with exclusive breastfeeding. Conclusion: Mother’s characteristics are not associated with exclusivebreastfeeding. Exclusive breastfeeding rate is still very low due to the highpractices of giving complementary food before infant aged six months oldand prelacteal food.Keywords : Exclusive breastfeeding, mother’s characteristic 1) Medical school, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan2) Department of Child Health, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan3) Department of Physiology, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan